Características do trabalho e sua associação com desfechos de peso e adiposidade: estudo transversal de base populacional - Jackeline Silva Cabral (2019)
Introduction: Evidence suggests association between labor characteristics such as night shift work, uninterrupted shift and being active at work with weight and adiposity outcomes. Objective: To analyze the association between work characteristics and weight and adiposity outcomes in the Brazilian population. Methodology: A cross-sectional and population-based study with data from the Pesquisa Nacional de Saúde (PNS) of 2013. The sample consisted of 36.247 Brazilians workers with 18 years old or more, who had weight, height and waist circumference measured, with exclusion of women who reported being pregnant or could not tell if they were pregnant. The outcome variables were overweight BMI ≥ 25 kg/m2, obesity BMI ≥ 30 kg/m2 and abdominal obesity (≥ 102 cm in men and ≥ 88 cm in women). Night work, uninterrupted shift work and being active at work were investigated as explanatory variables. Sociodemographic and lifestyle characteristics and years in the main work were analyzed as descriptive and adjustment variables. The analyzes were performed with help of the software Stata 14.0, considering the weights of the research sample design. Poisson regression models with robust variance were performed to estimate the association between main exposures and outcomes, considering the statistical significance level of 5%. Results: After adjusts, individuals who work at night and work in uninterrupted shifts respectively, presented a higher prevalence ratio for overweight (PR: 1.07 CI 95% 1.03-1.12; PR: 1.09 CI 95% 1.00-1.20), obesity (PR: 1.18 CI 95% 1.06–1.31; PR: 1.29 CI 95% 1.02-1.63) and abdominal obesity (RP: 1.12 IC95% 1.04-1.21; RP: 1.25 IC95% 1.06-1.48) when compared to those who work at conventional times. Being active at work was inversely associated with excess weight outcomes (PR: 0.92 IC95% 0.88-0.96), obesity (PR: 0.83 IC95% 0.75-0.92) and abdominal obesity (PR: 0.86 IC95% 0.81-0.92) in relation to those inactive at work. Final considerations: The results evidenced that night work, uninterrupted shift and being active at work may be potential risk factors for weight and adiposity outcomes.